An Environmental Study of Heavy Metals selected from Soils contaminated by Mines & Remnants of War in Basrah Governorate - Abdullah Hantoush, Researcher. Abdul Kareem; Ibrahim Al Hassen, Prof. Dr. Shukri (Basra studies journal, 2023)
This study aims to detect the presence and concentrations of some heavy metals in samples of soils contaminated with mines and military remnants in Basra Governorate. It also evaluate the spatial variation pattern of their concentrations and the extent of the contribution of mines and war remnants to soil contamination with these toxic elements. Three heavy metals were chosen to be examined: Fe, Pb, and Cu, because the metallic decomposition of mines and military remnants may contribute to the bulk of their pollution to the environment. Soil samples were collected during the period from January 2021 to March 2022, from 13 sites where there were remnants of mines and war remnants. The samples were examined using atomic absorption spectroscopy. The results showed that the concentrations of the selected heavy metals were high in most of the samples if they were compared with the reference sample. The maximum concentrations of Fe were 14510 µg/g for Fe, 249 µg/g for Pb, and 532.7 µg/g for Cu. These results indicate that the contamination of mines and military remnants has an effect on increasing the concentrations of these pollutants to such a large extent. Although there was no clear spatial pattern for the concentrations of these metals, the high concentration of these toxic pollutants may make the polluted lands environmentally hot spots.